Regulation of nerve‐evoked contractions of rabbit vas deferens by acetylcholine. Issue 9 (9th September 2015) - Wallace, Audrey; Gabriel, Deborah; McHale, Noel G.; Hollywood, Mark A.; Thornbury, Keith D.; Sergeant, Gerard P.
Abstract Stimulation of intramural nerves in the vas deferens of many species yields a classical biphasic contraction comprised of an initial fast component, mediated by P2X receptors and a second slower component, mediated by α1‐adrenoceptors. It is also recognized that sympathetic nerve‐mediated contractions of the vas deferens can be modulated by acetylcholine (Ach), however there is considerable disagreement in the literature regarding the precise contribution of cholinergic nerves to contraction of the vas deferens. In this study we examined the effect of cholinergic modulators on electric field stimulation (EFS)‐evoked contractions of rabbit vas deferens and on cytosolic Ca2+ levels in isolated vas deferens smooth muscle cells (VDSMC). The sustained component of EFS‐evoked contractions was inhibited by atropine and by the selective M3R antagonist, 1, 1‐dimethyl‐4‐diphenylacetoxypiperidinium iodide (4‐DAMP). EFS‐evoked contractions were potentiated by Ach, carbachol (Cch), and neostigmine. The sustained phase of the EFS‐evoked contraction was inhibited by prazosin, an α1‐adrenoceptor antagonist and guanethidine, an inhibitor of noradrenaline release, even in the continued presence of Ach, Cch or neostigmine. The soluble guanylate cyclase (sGC) inhibitor, 1H‐[1, 2, 4]Oxadiazolo[4, 3‐a]quinoxalin‐1‐one enhanced the amplitude of EFS‐evoked contractions and reduced the inhibitory effects of 4‐DAMP. Isolated VDSMC displayed spontaneous Ca2+ oscillations, but did not respond to Cch. However, the α1‐adrenoceptor agonist, phenylephrine, evoked a Ca2+ transient and contracted the cells. These data suggest that EFS‐evoked contractions of the rabbit vas deferens are potentiated by activation of M3 receptors and reduced by activation of a sGC‐dependent inhibitory pathway.